A systematic review on consumer behavior toward plastic consumption in Asian countries / Nur Syafiqah Khalisah Jallaludin ...[et al.] - Jallaludin, Nur Syafiqah Khalisah; Sukarno, Nor Shafieqa; Md Nasir, Siti Nur Baiyah; Ismail, Nur Ain; Amir Shah, Nur Aishah; Mohamat Sabri, Hanis Nadhirah; Mohammad, Noorita (Universiti Teknologi MARA, 2021)
The consumer's consumption of plastic continues to increase and has contributed to the global environmental concern, even though certain new environmental conservation policies or laws have been adopted and enforced. However, there were still insufficient studies that systematically review the existing literature on consumers in Asian Countries. Hence the present article conducted a systematic literature review on the plastic consumption behavior and the effect of plastic use by the customers. The present study joined multiple research designs and the review was based on the publication standard. (Reporting standards for systematic evidence syntheses). This study selected articles using two leading databases namely Scopus and Science Direct. Based on the thematic analysis, this review has three main themes namely 1) action to reduce plastic consumption; 2) waste management 3) impact of plastic on the ecosystem. The three main themes have further produced 11 sub-themes. The study offered several significant contributions for practical purposes and the body of knowledge. The findings explained the importance of integrating consumer awareness and knowledge into consumer plastic consumption, 1) to encourage respect for knowledge and the role played by the consumer on the usage of plastic consumption policy; 2) to strategize an adaptation plan that is in line with the needs, abilities, and intention to use plastic; and 3) to inform on effect on the ecosystem to the specific areas and content of researches that should be the focus of the future studies.